Politik Pencitraan Partai PDIP Jawa Barat terhadap Ganjar Pranowo dalam Menghadapi Pilpres 2024 - Purnama, Ahmad Dayu; Muhajir, Ahmad; Karimah, Ima Rahmatul (AHKAM, 2024)
This research investigates the political image strategy adopted by the West Java Indonesian Democratic Party of Struggle (PDIP) towards a potential figure, Ganjar Pranowo, in facing the 2024 Presidential Election. Based on a constructivist paradigm with a qualitative approach, this research uses a case study method with a focus on data triangulation. Involving in-depth interviews, content analysis and participant observation, the research aims to explore the political dynamics of imagery and its impact on public perception. The results of content analysis highlight political communication strategies, development of popular economic discourse, use of social media, and image construction through political advertising. The findings show the need to increase strategic integration with local values, the effectiveness of social media, and the concretization of community economic programs. While providing an in-depth look at the political image of the West Java PDIP, this research also presents insights that can contribute to the understanding of political strategy at the local and national level.